2020
DOI: 10.21873/anticanres.14648
|View full text |Cite
|
Sign up to set email alerts
|

Use of AKR1C1 and TKTL1 in the Diagnosis of Low-grade Squamous Intraepithelial Lesions from Mexican Women

Abstract: Background/Aim: To determine the differential protein profiles of cervical cancer cell lines in order to find potential targets that can be used as biomarkers in low-grade squamous intraepithelial lesions (LSIL) diagnosis. Materials and Methods: Proteomic analysis was performed on cervical cancer cell lines by 2D electrophoresis and liquid chromatography-mass spectrometry. Biomarker validation was performed in histological samples by immunofluorescence. Results: Aldo-keto reductase C1 (AKR1C1) and transketolas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Current study has shown that TKTL1 expression, which is increased in human endometrial cancer, is related to AKT phosphorylation level and GLUT1 [ 14 ]. In addition, the increased expression of TKTL1 has been proved to be a diagnostic marker in low-grade CC [ 15 ]. At the same time, study has confirmed that TKTL1 expression is increased in CC and can be used as a diagnostic marker for CC [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current study has shown that TKTL1 expression, which is increased in human endometrial cancer, is related to AKT phosphorylation level and GLUT1 [ 14 ]. In addition, the increased expression of TKTL1 has been proved to be a diagnostic marker in low-grade CC [ 15 ]. At the same time, study has confirmed that TKTL1 expression is increased in CC and can be used as a diagnostic marker for CC [ 16 ].…”
Section: Introductionmentioning
confidence: 99%